Labor mobility, social network effects, and innovative activity - Ulrich Kaiser; Hans Christian Kongsted; Thomas Rønde (Institute for the Study of Labor (IZA), 2011)
We study the mapping between labor mobility and industrial innovative activity for the population of R&D active Danish firms observed between 1999 and 2004. Our study documents a positive relationship between the number of workers who join a firm and the firm's innovative activity. This relationship is stronger if workers join from innovative firms. We also find evidence for positive feedback from workers who leave for an innovative firm, presumably because the worker who left stays in contact with their former colleagues. This implies that the positive feedback (social network effects) that has been found by other studies not only exists but even outweighs the disruption and loss of knowledge occurring to the previous employer from the worker leaving. Summing up the effects of joining and leaving workers, we find ample evidence for mobility to be associated with an increase in total innovative activity of the new and the old employer.
urn:nbn:de:101:1-201104213182
Keywords: O33; O34; C23; 330; labor mobility; innovation; social network; Arbeitsmobilität; Innovation; Industrielle Forschung; Soziales Netzwerk; Dänemark